Molecular Association of Sexually Transmitted Infections and Methylation Pattern of SNRPN Gene Promoter among Males with Abnormal Semen - Noor AL-Hamid; Abdul Kareem AL-Kazaz (Indian Journal of Forensic Medicine & Toxicology, 2021)
Infertility affects about 8-12% of couples worldwide, and male infertility accounts for a half of these cases, therefore, thisstudy was undertaken to focus on some factors affecting male’s fertility such as DNA methylation and genital tract infections by sexually transmitted diseases. The study groups included infertile males as a patient group (n=63) in an age mean (32.28 ± 6.88 years) and fertile males as a control group (n=13)in an age mean (34.07 ±6.52years).Seminal fluid was collected from all males attending a clinical laboratory for routine semen analysis, seminal fluid analysis was performed according to World Health Organization guidelines, all of the 63 infertile males was suffering from reduced sperm concentration (9.42 ± 8.70 million/ml), reduced progressive motility (2.89 ± 5.45%) and abnormal sperm morphology (27.06 ± 16.50%), while control group have a higher values thus, there was a highly significant difference in semen parameters between the two groups.The DNA samples of the patients group (n=44) and control group (n=13) was subjected to bisulfite treatment to convert un-methylated C-residues to uracil, this step was performed to allow the qualitative detection of methylation at the promoter of Small nuclear ribonucleoprotein polypeptide N gene by Real time polymerase chain reaction using two sets of designed primers (methylated and un-methylated sets) allowing one set of the primers to anneal, and amplify the desired region.The results of real time PCR for the detection of methylation in SNRPN gene promoter showed hyper methylation in the promoter of SNRPN in some samples (22.7%), a slight methylation in others (20.4%) and no methylation in other samples (56.8%) from infertile males, while all the 13 control samples showed no methylation.